1991
DOI: 10.1002/1097-0142(19911001)68:7<1465::aid-cncr2820680702>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

DNA flow cytometric analysis of primary operable breast cancer. Relation of ploidy and S-Phase fraction to outcome of patients in NSABP B-04

Abstract: Between 1971 and 1974, 1665 women with primary operable breast cancer were randomized into a National Surgical Adjuvant Breast and Bowel Project (NSABP) trial (B‐04) conducted to evaluate the effectiveness of several different regimens of surgical and radiation therapy. No systemic therapy was given. Cells from archival paraffin‐embedded tumor tissue taken from 398 patients were analyzed for ploidy and S‐phase fraction (SPF) using flow cytometry. Characteristics and outcome of patients with satisfactory DNA hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
2
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(29 citation statements)
references
References 35 publications
3
22
2
2
Order By: Relevance
“…Seven large series (> 300 patients) with long follow up () 5 years median) have used multivariate analysis to assess the independence of observed effects, but with variable results (Cornelisse et al, 1987;Hedley et al, 1987;Kallionemi et al, 1988;Clark et al, 1989;Toikkanen et al, 1989;Stal et al, 1989;Fisher et al, 1991). We have studied these variables in a large cohort of homogeneously treated patients with breast cancer who have been followed up for a median period of over 10 years, paying particular attention to technical factors which may be responsible for the varying results obtained by previous workers, and report here upon this experience.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Seven large series (> 300 patients) with long follow up () 5 years median) have used multivariate analysis to assess the independence of observed effects, but with variable results (Cornelisse et al, 1987;Hedley et al, 1987;Kallionemi et al, 1988;Clark et al, 1989;Toikkanen et al, 1989;Stal et al, 1989;Fisher et al, 1991). We have studied these variables in a large cohort of homogeneously treated patients with breast cancer who have been followed up for a median period of over 10 years, paying particular attention to technical factors which may be responsible for the varying results obtained by previous workers, and report here upon this experience.…”
contrasting
confidence: 57%
“…Ploidy and SPF could be combined to create three prognostic groups which were independent predictors of survival, although once again this relied upon cutoffs determined by examination of the data. Finally, Fisher et al (1991) have reported upon results from the NSABP-04 trial in 398 patients. This represented only 54% of available tumour blocks, the remainder failing to provide adequate histograms.…”
Section: Spfmentioning
confidence: 99%
“…Tumour cell proliferation has been shown to be a prognostic marker in some reports (Remvikos et al, 1989;Bonetti et al, 1996;Chevillard et al, 1996), but data on its predictive value are conflicting. S-phase fraction, proliferating cell nuclear antigen and thymidine labelling index predict overall survival (Clayton, 1991;Fisher et al, 1991;Merkel et al, 1993) and response (Collecchi et al, 1996;Bottini et al, 1998;Nishimura et al, 2002), but not diseasefree survival (Bianchi et al, 1993;Pisansky et al, 1993;Tahan et al, 1993) in patients treated with primary surgery or chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…However, the attempts to isolate and identify specific protein failed [1,3]. It can be hypothesized that not individual protein, but a complex of proteins exhibits biological activity.…”
mentioning
confidence: 99%